The Guitar and its Music From the Renaissance to the Classical Era. - Hindrichs, Thorsten (Oxford University Press, Oxford, 2004)
RESUMEN: Autores James Tyler and Paul Sparks. Oxford Early Music Series. Oxford University Press, Oxford and New York, 2002